Droughts and low water levels in late medieval Hungary II: 1361, 1439, 1443-4, 1455, 1473, 1480, 1482(?), 1502-3, 1506: Documentary versus tree-ring (OWDA) evidence - Kiss, Andrea (Journal of Environmental Geography, 2017)
As a continuation of the first paper from the late medieval drought series related to medieval Hungary, we present, analyse and compare further late medieval drought data, based on contemporary direct and indirect written sources. The evidence derived from documentary sources referring to the droughts and dry spells in 1361, 1439, 1473, 1480, 1482(?), 1502-1503 and 1506 are further compared to the recent tree-ring based hydroclimate reconstruction of the OWDA (Old World Drought Atlas), and similarities, differences and complementary information are discussed in more detail. Additionally, documentary evidence related to Danube low water-levels of 1443, 1444, 1455 and 1502 are as well presented in a broader context: these cases provide evidence on the hydrological conditions of the Upper-Danube catchment, and not on the Carpathian Basin. The OWDA evidence in most cases shows good agreement with the discussed documentary-based drought reports, some differences in the spatial extension and intensity of the drought were only exceptionally detected (e.g. 1455, 1507). Most of the written documentation refer to droughts that covered more than one calendar years.